PELAKSANAAN KEBIJAKAN MENGENAI FASILITAS PEJALAN KAKI DI KOTA PEKANBARU TAHUN 2013 - Era Elfiandi; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Population growth and high population densities caused providing pedestrian of transportation such as people crossing bridge, have started in several locations of congested traffic. People crossing bridge is intended to facilitate the pedestrians to cross the road in comfort and safety.This is a descriptive study using a qualitative approach as a tool of analysis. The research was conducted at Pekanbaru, with a focus of research on the implementation of policie sregarding pedestrian facilities such as people crossing bridge in Pekanbaru and factors that affectingthe implementation of policies about people crossing bridge didn’t maximal which used the theory by Edward III. Techniques of data collection were interviews, observati on and documentation.After research, the authors conclude that implementation of policies about people crossing bridges didn’t maximal because the existence of a people crossing bridges was rarely used and often miss functioned. The affecting factors of didn’t maximalis less effective communication, the limited available resources, the attitude of implementator. The factors that most influence implementation of policies about people crossing bridges are resource constraints such as budget or funds that have not been owned by the Pekanbaru government and there isn’t punishment to the existence of people crossing bridges that violates the rules and functioned incorrectly.Keyword : Implementation, PeopleCrossingBridge, Policy.